SPEECH ACTS ANALYSIS OF PRE-SERVICE TEACHERS AND STUDENTS AT SMK NEGERI 1 SINGARAJA - Kadek Dhea Paramitha Amara Putri; I Nyoman Adi Jaya Putra; Dewa Putu Ramendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This research aims to analyze the kind of speech act used by pre-service teachers and studentsof SMK Negeri 1 Singaraja in WhatsApp as learning media. Investigate the most dominant speech actused by pre-service teachers and students, and analyze the kind of instructional function used by thepre-service teachers. The data were analyzed using descriptive qualitative. The subject of this researchis the pre-service teacher and students in SMK Negeri 1 Singaraja. The data were collected throughobservation and interview. The data from the observation was collected using an observation sheetwhich developed from Searle’s (1969) theory of speech act and Johnson’s (1997) theory of instructionalfunction. The interview has been done semi-structured using an interview guide. The result showsthat the pre-service teacher use four speech act in the learning activity; representative, directive,commissive, and expressive. The pre-service teacher uses directive speech to act dominantly to makethe students active in the learning process. Meanwhile, the students use four speech act, includingrepresentative, directive, commissive, and expressive. The students use representative in dominant tobe active and getting feedback in the learning activity. The kinds of the instructional function used bythe pre-service teacher are control, organize, and motivational. It was found that the directive speechact functioned as control. Commissive functioned as organize. And expressive as motivationalfunction.